ESG score analysis as an indicator for investment decisions and sustainable growth - Setiyaningsih, Eva; Meini, Zumratul; Dospinescu, Octavian (Ifma Publishing, 2025)
ESG is a principle that prioritizes sustainable development, investment and business activities in accordance with three criteria, namely environmental, social and governance. ESG (environment, social, governance) scores are a benchmark for evaluating sustainability in an entity. ESG scores can be used to certify an entity's sustainable development and other types of sustainability. On the other hand, more and more literature is found showing that ESG scores are unable to measure sustainability in terms of sustainable development. The main reason this occurs is due to an entity's inability to understand ESG principles, resulting in greenwashing practices. In this literature review, descriptive qualitative methods are used. The aim of this literature review is to examine the challenges and problems related to ESG and the phenomenon of greenwashing practices. Indirectly, greenwashing practices increase ESG scores, but if we look at the proper factors, this can be considered to violate ESG principles. It is hoped that this literature review will help future research regarding ESG factors that influence business investment and sustainability.